2007
DOI: 10.1644/05-mamm-a-409r.1
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Molecular Relationships between Zarudny's Rock Shrew (Crocidura zarudnyi; Mammalia: Soricomorpha) and Eurasian Taxa

Abstract: We karyotyped and sequenced 1,140 base pairs of the mitochondrial DNA cytochrome b of a specimen of Zarudny's rock shrew (Crocidura zarudnyi) from Baluchestan, southeastern Iran, to clarify its cytogenetic and molecular relationships with other Eurasian species of Crocidura. According to the karyotype (2N ¼ 40, FN ¼ 50), Zarudny's rock shrew belongs to the group of the lesser white-toothed shrew (C. suaveolens), which is different from other known crocidurine karyotypes, considering the combination of the dipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The cytochrome-b sequences (399 bp) of the three analysed individuals were identical (Genbank accession number: KC590097) and closely related to the previously published sequence of C. zarudnyi from Baluchestan (Genbank accession number: EF524711; Dubey, Nová et al 2007), confirming our morphological identification (K2P distance: 0.3%, corresponding to one transition in position 161 {KC590097: T and EF524711: C}; see…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The cytochrome-b sequences (399 bp) of the three analysed individuals were identical (Genbank accession number: KC590097) and closely related to the previously published sequence of C. zarudnyi from Baluchestan (Genbank accession number: EF524711; Dubey, Nová et al 2007), confirming our morphological identification (K2P distance: 0.3%, corresponding to one transition in position 161 {KC590097: T and EF524711: C}; see…”
supporting
confidence: 85%
“…The Zarudny's rock shrew, Crocidura zarudnyi, was described by Ognev, 1928 based on a single specimen from the Baluchestan province in southeastern Iran and is currently known from very few localities in Afghanistan, Pakistan and Iran (Hassinger 1970;De Roguin 1988;Hutterer 2005;Dubey, Nová et al 2007). It was only recently found that an additional specimen had been recorded in Pir sohrab, Chabahar in southeastern Iran (Baluchestan) and characterised morphologically, genetically and karyotypically by Dubey, Nová et al (2007). The latter study revealed that C. zarudnyi is closely related to the widespread C. suaveolens group (see e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the cytochrome b, the genetic divergence found between the two geographical samples (4.1%) (Zambia and Burundi) is at the boundary between the values that distinguish different species as well as populations of the same species in Crocidura (Dubey et al , 2007a(Dubey et al , 2007b. The 16S rDNA, which is characterized by a low mutation rate with respect to cytochrome b, is even more similar between the two samples with only 5 substitutions out of 470 bp.…”
Section: Discussionmentioning
confidence: 88%
“…Over a vast area stretching across all of Eurasia from the Iberian Peninsula to Tsushima Island through several natural zones, all forms of the Lesser Whitetoothed Shrew, except for С. sibirica, have identical karyotypes (Grafodatsky et al, 1988), and many authors believe that all populations with 2n = 40 on this territory should be considered a single species C. suaveolens (Catzeflis et al, 1985;Vogel et al, 1986;Hutterer, 1993). However, there is also evidence of morphological (Zaitsev, 1991;Tembotova, 1999;Bannikova et al, 2001;Jiang and Hoffmann, 2001) and high molecular (Vogel et al, 2003;Ohdachi et al, 2004;Bannikova et al, 2006;Dubey et al, 2006Dubey et al, , 2007aDubey et al, , 2007b diversity of this group. At present, no fewer than seven forms are recognized within the "Lesser White-toothed Shrew" species group according to morphological data and mitochondrial DNA (mtDNA) sequences; however, the views on the species status of these form vary among different authors.…”
Section: Introductionmentioning
confidence: 97%